Parameter estimation problems in physically based image processing - Klinger, Matthias (Numerical Mathematics and Advanced Applications 2011, 2013)
In this contribution we consider an optimization problem constrained by a system of state equations coupling the nonstationary model for gray-value transport in an image sequence to the physical model of a transport field resulting in the gray-value evolution. Since in this situation the movement over the boundaries is often unknown, we use a Dirichlet-boundary control formulation for the determination of the transport field.